Financial and economic mechanisms of urban agglomeration - N. K. Popadyuk (Вестник университета)
The subject of the study is the search for mechanisms of financial and economic regulation of the development of urban agglomeration, which, due to the chronic insufficiency of funds for these purposes of municipal budgets, is of particular importance.   The purpose of the work is to justify the need to use non-traditional tools for regulating the coordinated development of municipalities forming the urban agglomeration.   At the same time, it is shown that not only state regional government and municipal self-government bodies are the subjects of economic activity in each urban agglomeration: among them there are quite independent economic entities that need to be invited on the principles of public-private and municipal-private partnership to participate in the coordinated management of the development of the entire agglomeration in the interests of all stakeholders. The study is conducted on the basis of generalisation of the literature on the analysis of the methods used to manage the development of the urban agglomerations. Publications in which the analysed problems found forms of their resolution are the sources of information. The results of the study have heuristic potential due to the possibility of using the considered tools for financing the development of agglomeration for the coordinated development of the municipalities that do not form the urban agglomeration.   The possibility of applying non-traditional forms of financing the coordinated development by increasing the capitalisation of municipal assets is the conclusion of the study.   The relevance of the considered topic is due to the need to ensure the use of the entire arsenal of market instruments for purposeful development of the municipalities at a new stage of state development.